Inovasi Eceng Gondok sebagai Alternatif Pakan Ternak Unggas - Muhammad Ridwan Dwi Nugroho; Alfino Rizky Indrawan; Lutfiana Rochmah; Widya Shafira Apriliani; Bellachintya Reira Christata (Muria Jurnal Layanan Masyarakat, 2026)
Water hyacinth is an aquatic plant that is often considered a weed because of its rapid growth and can disturb aquatic ecosystems. However, water hyacinth has great potential as an alternative livestock feed, especially for poultry, because of nutritional content such as protein, fiber, and carotenoids which are quite high. This article discusses the innovation of utilizing water hyacinth in Kirig Village as poultry livestock feed through a fermentation process that increases the nutritional value and digestibility of the feed. The fermentation method using microorganisms and natural materials such as molasses aims to improve feed quality and accelerate the growth of poultry livestock. This program not only helps overcome the problem of water hyacinth as a weed, but also supports food security and the sustainability of livestock businesses in the village. The results of the training and socialization show the enthusiasm of the community in adopting this innovation as a practical and economical solution in poultry livestock cultivation at the local level.